Design and Development of an Internet of Things (IoT)–Based Parking Lot Monitoring System - TRI YOLANDA; FATONI (Institute of Information Technology and Social Science (IITSS), 2024)
The rapid advancement of the Internet of Things (IoT) has enabled the development of smart systems that automate various aspects of urban infrastructure, including parking management. This study aims to design and implement an IoT-based parking lot monitoring system that assists drivers in identifying available parking spaces and locating them accurately within a parking area. The system provides real-time information regarding slot availability through a display installed at the entrance gate. The prototype employs an ESP32 microcontroller, ultrasonic sensors, a PIR (Passive Infrared) sensor, a servo motor, LED indicators, and a buzzer as the main hardware components. The system software was developed using the Arduino IDE for embedded programming and Microsoft Visual Studio (C#) for the desktop monitoring application. System testing demonstrates that the prototype successfully delivers real-time information on parking slot occupancy and overall parking capacity. The proposed system enhances the effectiveness and efficiency of parking management for both operators and users.